Democratic Republic of Sao Tome and Principe : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; and Press Release on the Executive Board Consideration. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
In 2005, the overall macroeconomic performance was broadly satisfactory, notwithstanding an increase in inflation. All performance criteria were met. Structural reforms advanced, and delays in preparing feasibility studies for restructuring the airport and seaport authorities are being addressed. Economic performance in 2005 was broadly satisfactory, although inflation accelerated. The fiscal program is designed to protect pro-poor spending. The program assumes a broadly stable velocity of circulation of money. The macroeconomic outlook and the program are subject to risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet